2020
DOI: 10.3390/su12219133
|View full text |Cite
|
Sign up to set email alerts
|

Family Coping Strategies During Finland’s COVID-19 Lockdown

Abstract: During spring 2020, the COVID-19 pandemic and global lockdowns fundamentally changed families’ everyday lives. This study aims to examine how families with children coped during the COVID-19 lockdown in Finland and what kind of coping strategies they developed. An online survey including both qualitative and quantitative questions was conducted between April and May 2020 to gather Finnish families’ experiences during the COVID-19 lockdown. In this study, we focus on information from one open-ended question, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 24 publications
6
66
0
9
Order By: Relevance
“…Stress management strategies, e.g. stress reappraisal and mindfulness can help, and it is important for formal mental health services provided by family therapists, educators or health care professionals need to take into account of the diversity of distressed families’ care needs ( Salin et al, 2020 ). Family coping strategies developed during the Covid-19 lockdown, such as agreements about everyday practices, flexibility in daily routines, family time, and family conversation, are crucial for families’ everyday lives which may have been significantly altered during the pandemic ( Salin et al, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Stress management strategies, e.g. stress reappraisal and mindfulness can help, and it is important for formal mental health services provided by family therapists, educators or health care professionals need to take into account of the diversity of distressed families’ care needs ( Salin et al, 2020 ). Family coping strategies developed during the Covid-19 lockdown, such as agreements about everyday practices, flexibility in daily routines, family time, and family conversation, are crucial for families’ everyday lives which may have been significantly altered during the pandemic ( Salin et al, 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Four types of coping strategies i.e., acceptance, humanitarian, mental disengagement, and seeking social support were examined. Salin et al [ 27 ] mention that most common emotion-focused coping method “adopted among the youth was acceptance.” Acceptance is “intended to disrupt the link between thoughts and behaviours to tolerate painful stimulation” [ 28 ]. The acceptance strategy involves a coping method that resolves into accepting the stressor in question.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some NHS trusts have already begun to champion this style of consultation and by raising awareness and increasing the availability of this service may help to remedy the effects of lockdown (29). Moreover, a study from Finland demonstrated that coping mechanisms which emanated from close personal relationships proved to be the most significant strategy to maintain psychological well-being during the COVID crisis (30). Therefore, by increasing access and education relating to virtual communication platforms, which allow family units to stay connected, may prove beneficial.…”
Section: Discussionmentioning
confidence: 99%